2001
DOI: 10.1046/j.1469-8137.2001.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

UV and blue light signalling: pathways regulating chalcone synthase gene expression in Arabidopsis

Abstract: SummaryUV-B, UV-A and blue light control a variety of aspects of plant development via distinct photoreceptors and signalling pathways. The known photoreceptors for UV-A/ blue light are cryptochrome (cry)1 and cry2, and the phototropism photoreceptor, phototropin. Redox processes are important in cry and phototropin signal transduction. A specific photoreceptor for UV-B has not been identified and there appear to be several possible UV-B signalling pathways. We are investigating the UV and blue light regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 80 publications
9
101
2
2
Order By: Relevance
“…9E). These results were in conformity with earlier studies in which a 10-fold increase in CHS expression of mature Arabidopsis leaves was reported (Jenkins et al, 2001). The lower transcript level of ReCHS1 as compared with that of ReCHS2 correlates with earlier studies on G. max in which only the CHS1 member of the gene family showed induction Figure 6.…”
Section: Effects Of Abiotic Elicitors On Rechs Expression Vis-à-vis Fsupporting
confidence: 92%
See 1 more Smart Citation
“…9E). These results were in conformity with earlier studies in which a 10-fold increase in CHS expression of mature Arabidopsis leaves was reported (Jenkins et al, 2001). The lower transcript level of ReCHS1 as compared with that of ReCHS2 correlates with earlier studies on G. max in which only the CHS1 member of the gene family showed induction Figure 6.…”
Section: Effects Of Abiotic Elicitors On Rechs Expression Vis-à-vis Fsupporting
confidence: 92%
“…It was first shown in Arabidopsis (Arabidopsis thaliana) that UV and blue light could induce the expression of CHS genes (Jenkins et al, 2001). The plant tissues treated with UV light showed a gradual increase in the expression of ReCHS1 up to a maximum of 2-fold at 9 h post induction, whereas a steep increase was observed in the transcript level of ReCHS2, which showed a nearly 5-fold increase at 6 h followed by a 12-fold increase at 9 h (Fig.…”
Section: Effects Of Abiotic Elicitors On Rechs Expression Vis-à-vis Fmentioning
confidence: 99%
“…At the molecular level, the CHS gene encoding a key enzyme in flavonoid biosynthesis, chalcone synthase, is known to be induced by UV-B (e.g., Jenkins et al, 2001). Moreover, the HY5 protein was previously shown to bind CHS promoter sequences in vitro (Ang et al, 1998).…”
Section: Cop1 and Hy5 Are Required For Uv-b-mediated Hypocotyl Growthmentioning
confidence: 99%
“…This includes hypocotyl growth inhibition, flavonoid accumulation, and specific gene expression changes. A rather well-characterized gene activated by low levels of UV-B is CHALCONE SYNTHASE (CHS), encoding a key enzyme of phenylpropanoid biosynthesis (Jenkins et al, 2001). On a genome-wide level, recent array analyses for plant responses to UV-B radiation identified a broad range of activated and repressed genes that may now be linked to UV-B responses (e.g., Casati and Walbot, 2004;Ulm et al, 2004;Ulm and Nagy, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has often been speculated that UV-B may be perceived by a novel class of photoreceptor, but no such molecule has ever been identified. Moreover, although pharmacological, cell physiological, and genetic approaches have provided some insights into UV-B signal transduction processes (15)(16)(17), no UV-B-specific signaling pathway has been defined. Thus, understanding of the mechanisms of plant UV-B responses lags well behind knowledge of light responses mediated by the phytochrome, cryptochrome, and phototropin photoreceptors.…”
mentioning
confidence: 99%